Remembering Another Aspect of Forgetting - Jasnow, Aaron M.; Cullen, Patrick K.; Riccio, David C. (Frontiers in Psychology, 2012)
Although forgetting is most often thought of in terms of declines in performance (response loss or impairment), another class of memory phenomena, the forgetting of stimulus attributes, has begun to attract experimental attention. In nonhuman animals, the loss of memory for stimulus features is reflected in the flattening of stimulus generalization gradients as well as in the attenuation of the disrupting effect of a shift in context at testing. In both cases, a delay between the learning episode and testing results in increased responding in the presence of previously ineffective stimuli. Thus, previously discriminable cues become more functionally interchangeable. The implications of the forgetting of attributes for some theoretical issues of memory loss and for methodological strategies have been noted earlier. However, relatively little is known about the neurobiological mechanisms underlying stimulus attribute forgetting, and why some memories are maintained while others are not. In this paper we review the evidence for the forgetting of stimulus attributes, discuss recent findings identifying neurobiological underpinnings of forgetting and generalization of fear responses, and discuss relevant clinical implications of fear generalization.